2022
DOI: 10.3389/fpubh.2022.909766
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity and energy expenditure of a multicomponent home-based training program: Xiangya hospital circuit training (X-CircuiT)

Abstract: IntroductionOur previous studies showed that Xiangya Hospital Circuit Training (X-CircuiT) effectively improved physical fitness and reversed pre-frailty in community-dwelling older adults. This study aimed to explore the generalizability and applicability of X-CircuiT in different aged populations in the context of exercise intensity and energy expenditure.MethodsWe prospectively recruited 72 community-dwelling sedentary adults, twelve adults divided into 6 age groups ranging from 20 to 80 years old and separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…For example, EE estimation with 5-min window achieves the best performance in EXER high , while the one with 19-min window shows the best performance in EXER low . Indeed, high-intensity exercises elevate participants' metabolic rates to a greater extent than low-intensity exercises [27]. Aggregating data over extended periods might obscure the dynamic shifts that occur in shorter time frames.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EE estimation with 5-min window achieves the best performance in EXER high , while the one with 19-min window shows the best performance in EXER low . Indeed, high-intensity exercises elevate participants' metabolic rates to a greater extent than low-intensity exercises [27]. Aggregating data over extended periods might obscure the dynamic shifts that occur in shorter time frames.…”
Section: Discussionmentioning
confidence: 99%
“…An umbrella review with 27 systematic reviews and 28,205 participants showed that PA was significantly associated with cognitive and noncognitive outcomes among individuals with MCI ( 7 ). The Xiangya Hospital circuit training (X-CircuiT), a multicomponent exercise program developed by the cardiac rehabilitation team based on current multinational guidelines, could take into account the PA preferences of older adults with pre-frailty and effectively reverse pre-frailty ( 8 , 9 ). The potential mechanisms by which PA promotes cognitive function include the release of growth factors, inflammatory cytokines, neuroplasticity across the brain, the production of lactate, increased mitochondrial biogenesis, and enhanced activity of the antioxidant enzyme ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%